The Mutagenic Effect of UVC Irradiation on Viability and Antibiotic Susceptibility in Pseudomonas aeruginosa Isolated from Clinical Cases - Saleh, Bushra H; Al-Ugaili, Dhafar N. (Iraqi Journal of Science, 2025)
Pseudomonas aeruginosa is a notorious opportunistic pathogen that frequently causes hospital-acquired infections, particularly in burn wounds and urinary tract infections, and is consistently ranked among the top three most common Gram-negative pathogens associated with these types of infections. During a period of 4 months, from 8/2021 to 11/2021, 65 samples were collected from patients suffered from burns, wounds, and UTIs infections in three hospitals in Baghdad. The conventional cultural identity of the isolates was confirmed by the results of the VITEK 2 system. Molecular identification of P. aeruginosa isolates based on 16S rRNA gene amplification and sequencing was done, followed by testing antibiotic susceptibility profile for the isolates. Ultraviolet C (UVC) was employed to cause mutations in five P. aeruginosa isolates at different times (30, 90, 180, and 360 seconds) by using the UV transilluminator. The results of the mutation revealed that the viability of all five isolates decreased over time after exposure to UV light at various time periods. Notably, the P1 isolate exhibited a significantly stronger response to UVC radiation compared to the other four isolates, suggesting a unique sensitivity to this type of mutagenic stress. Mutated P. aeruginosa P1 isolate revealed that while bacterial cell viability decreased within time, the isolate became more sensitive toward the antibiotics ciprofloxacin, colistin, gentamycin, and Imipenem after mutation for different times. Additionally, P1 isolates showed changes in responses from resistant to susceptible toward the antibiotics Aztreonam, Cefotaxime , and Levofloxacin, while other antibiotics like Piperacillin-tazobactum ,Ceftriaxone and Ceftazidime showed the same results in P1 isolates before and after mutation.